Efektifitas Pupuk Bersubsidi Terhadap Peningkatan Produktivitas Padi Sawah - U Maman; Iwan Aminudin; Erisca Novriana (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2021)
The Effectiveness of Subsidised Fertilizer on Increasing the Productivity of Rice Rice. This research was conducted to analyze the effectiveness of subsidized fertilizers to increase the productivity of lowland rice in Indonesia. The subsidized fertilizers include Urea, SP-36, ZA, NPK, and organic fertilizers. The data used in this research is secondary data. The data used are time series data consisting of lowland rice productivity data, a realization of subsidized fertilizers consisting of Urea, SP-36, ZA, NPK, and organic fertilizers obtained from various sources including BPS, Ministry of Agriculture, and institutions. other related. Based on the results of the simultaneous analysis to determine the effect of the realization of subsidized fertilizers on increasing the productivity of lowland rice in Indonesia in Table 5.6, it can be seen that the calculated F value is 27.908 and sig. <0.000. The calculated F value is greater than the F table (2,2364) and the sig value. = 0.000 is smaller than α = 0.05. It can be concluded that simultaneously (together / as a whole) subsidized fertilizers affect lowland rice productivity.